Understanding energy-related regimes: A participatory approach from central Australia. (April 2016) - Foran, Tira; Fleming, David; Spandonide, Bruno; Williams, Rachel; Race, Digby
Abstract: For a particular community, what energy-related innovations constitute no-regrets strategies? We present a methodology to understand how alternative energy consuming activities and policy regimes impact on current and future liveability of socio-culturally diverse communities facing climate change. Our methodology augments the energy policy literature by harnessing three concepts (collaborative governance, innovation and political economic regime of provisioning) to support dialogue around changing energy-related activities. We convened workshops in Alice Springs, Australia to build capability to identify no-regrets energy-related housing or transport activities and strategies. In preparation, we interviewed policy actors and constructed three new housing-related future scenarios. After discussing the scenarios, policy and research actors prioritised five socio-technical activities or strategies. Evaluations indicate participants enjoyed opportunities given by the methodology to have focussed discussions about activities and innovation, while requesting more socially nuanced scenario storylines. We discuss implications for theory and technique development. Highlights: Energy-related activities and regimes frustrate pro-sustainability action. Participatory workshops increased understanding of activities and regimes. Workshops used a novel combination of governance and social theories. Results justify inclusive dialogue around building energy standards and transport options.